THE PLANT STUDY OF GUNUNG SARI UNM CAMPUS AREA AS A HIGHER PLANT BOTANY LEARNING RESOURCES - Mushawwir Taiyeb; Syamsiah, Syamsiah; Lodang, Hamka (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2023)
Abstract: The study aimed to describe the diversity of flora in the UNM Gunung Sari Campus area. This research is qualitative descriptive research, namely research conducted by describing the research data that have been carried out systematically and accurately regarding the characteristics of higher plants with varied habitus, such as herbs, bushes, shrubs, and trees. The observation of plants was carried out by roaming method by exploring all research locations. The data collection techniques were conducted by carrying out direct identification in the field, and further identification for unknown species concerning literature/ books, identification keys, and plantNet applications. In addition, the documentation was carried out by taking pictures of each plant sample found, both habitus pictures and pictures of each organ. The results of the study revealed that the flora of the UNM Gunung Sari Campus area was quite diverse consisting of 121 species belonging to 51 families, representing all of the higher plants, Pinophyta division (open seed plant group/Gymnosperm) and Magnoliophyta division (closed seed plant group/ Angiosperm), included in the class of Magnoliopsida (Dicotyledon), class of Liliopsida (Monocotyledon). All of these species represent all habitus categories, namely herbs, bushes, shrubs, and trees. Thus, the flora in UNM Gunung Sari Campus Area is representative to serve as a source of learning for several Botany hump courses in the Department of Biology. Abstrak: Tujuan penelitian adalah untuk mengetahui gambaran keragaman flora di kawasan Kampus UNM Gunung Sari. Penelitian ini merupakan penelitian deskriptif kualitatif yaitu penelitian yang dilakukan dengan menggambarkan dan mendeskripsikan data hasil penelitian yang telah dilakukan secara sistematis dan akurat mengenai ciri-ciri tumbuhan tingkat tinggi dengan habitus bervariasi, seperti herba, semak, perdu, dan pohon. Pengamatan tumbuhan dilakukan dengan metode jelajah dengan menjelajahi seluruh lokasi penelitian. Teknik pengambilan data dengan melakukan identifikasi langsung di lapangan, dan identifikasi lanjutan untuk spesies yang belum diketahui dengan mengacu pada literatur/ buku, kunci identifikasi, dan aplikasi plantNet. Di samping itu dilakukan dokumentasi dengan pengambilan gambar setiap sampel tumbuhan yang ditemukan, baik gambar habitus maupun gambar setiap organ. Hasil penelitian mengungkapkan bahwa flora Kawasan Kampus UNM Gunung Sari cukup beragam terdiri dari 121 species termasuk ke dalam 51 familia, mewakili tumbuhan tingkat tinggi yaitu divisio Pinophyta (tumbuhan biji terbuka/Gymnospermae) dan divisio Magnoliophyta (tumbuhan biji tertutup/Angiosperm), tercakup dalam classis Magnoliopsida (Dicotyledonae), classis Liliopsida (Monocotyledonae). Semua species tersebut mewakili kategori habitus, yaitu herba, semak, perdu, dan pohon. Dengan demikian flora pada Kawasan Kampus UNM Gunung Sari representatif untuk dijadikan sebagai sumber belajar beberapa mata kuliah Botani pada Jurusan Biologi.